Backbone and sterospecific methyl side chain resonance assignments of the homodimeric zinc sensor AdcR (32 kDa) in the apo- and Zn(II)-bound states - Guerra, Alfredo J. (2012)
Streptococcus pneumoniae adhesin competence repressor (AdcR) is a Zn(II)-dependent 32 kDa homodimer that controls the transcription of a zinc-specific ABC uptake system (AdcABC), three pneumococcal histidine triad proteins (PhtA, PhtD and PhtE), and an AdcA homolog AdcAII. AdcR is the first metal-dependent member of the MarR family of prokaryotic transcriptional repressors. Two-dimensional NMR studies reveal large changes in the spectrum upon Zn(II) binding. Near complete backbone and stereospecific methyl group resonance assignments for apo- and Zn(II)-AdcR are presented here.